SISTEM INFORMASI PENDATAAN FAKIR MISKIN DAN ANAK YATIM PADA KANTOR DESA TUMPOK LAMPOH KECAMATAN KUTA BARO KABUPATEN ACEH BESAR - Fainun, Ahmad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2020)
Tumpok Lampoh Village Office, Kuta Baro Subdistrict, Aceh Besar District records the data of the poor and orphans according to the direction of financial assistance for the poor as recipients of government assistance and in accordance with the recommendations of the Aceh Qanun Draft Empowerment of Orphans and the Poor. The limitation of the problem is only on the Information System for Data Collection of the Poor and Orphans at the Tumpok Lampoh Village Office, Kuta Baro District, Aceh Besar Regency, in order to realize the information system using Visual Basic applications and the purpose of writing here consists of general goals and special objectives. There are two methods that the authors use to collect data, namely Field Study and Library Research. Based on observations and writers can draw a conclusion Information System for Data Collection of the Poor and Orphans at the Tumpok Lampoh Village Office, Kuta Baro District, Aceh Besar Regency is expected to help make data collection of the poor and orphans who are accurate and effective and built using Visual Basic and Microsoft Access as the database.